Developing an Ethnoscience-Based Physics Learning Model based on Indonesian Local Wisdom to Strengthen Patriotism - Ahmad Fahrudin; Astri Riance; Eka Maryam (MAN 4 Kota Pekanbaru, 2026)
This study aims to develop an ethnoscience-based physics learning model that is valid, practical, and effective in strengthening students’ character of love for the homeland. The background of this research is the need for contextual physics learning that integrates local wisdom to enhance students’ conceptual understanding while supporting character education. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of the study were senior high school students and physics teachers. Data were collected using expert validation sheets, teacher and student response questionnaires, and an instrument to assess students’ patriotism character. The results showed that the developed learning model achieved a very valid category with an average validation score of 4.39. The practicality test indicated very practical criteria, with teacher and student response percentages of 86.4% and 85.0%, respectively. Model effectiveness was measured through a pretest–posttest analysis of students' increase in patriotism on a 1–5 Likert scale across all patriotism indicators. The normalized gain (N-Gain) was 0.52, indicating a moderate improvement. These findings indicate that the ethnoscience-based physics learning model is feasible and effective as an innovative approach to physics learning that integrates local culture and strengthens students’ character of love for the homeland.